2012
DOI: 10.1016/j.healthplace.2012.07.007
|View full text |Cite
|
Sign up to set email alerts
|

County-level determinants of dental utilization for Medicaid-enrolled children with chronic conditions: How does place affect use?

Abstract: Little is known about how place affects childrens’ access to dental care. We analyzed data for 25,908 Iowa Medicaid-enrolled children with chronic conditions to identify the county-level determinants of dental utilization. Our analyses suggest that higher levels of poverty and designation as a dental health professional shortage area at the county-level are associated with lower probability of child-level dental use. There are significant interactions between child-level race/ethnicity and county-level poverty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 61 publications
(60 reference statements)
3
23
0
Order By: Relevance
“…Our finding from the multivariable model that children living in rural areas were less likely to receive dental care agrees with previous research (Beil et al, 2012;Chi et al, 2010;Chi and Leroux, 2012). However, the interesting associations seen between race and utilization of dental care hint at complex relationships that are worth further investigation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our finding from the multivariable model that children living in rural areas were less likely to receive dental care agrees with previous research (Beil et al, 2012;Chi et al, 2010;Chi and Leroux, 2012). However, the interesting associations seen between race and utilization of dental care hint at complex relationships that are worth further investigation.…”
Section: Discussionsupporting
confidence: 90%
“…One recent study of dental expenditures among Medicaid-enrolled children found higher rates of preventive visits in counties with higher dentist supplies (Beil et al, 2012). Another recent study of dental utilization among Medicaid-enrolled children with chronic conditions found that utilization of dental services was lower in counties with dental Health Professional Shortage Area (HPSA) designations (Chi and Leroux, 2012). While both studies examined the role of county urbanicity, other measures should be considered in order to evaluate the role of spatial accessibility.…”
Section: Spatial Accessibility Is Influenced By Dentist Availability mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is different from those in previous studies in which investigators examined dental care utilization among children and adolescents to find a statistically significant effect of community poverty. 16,17 The results from our study imply that dental care utilization in poor communities is lower because of the individual-level characteristics of residents in the community rather than because of neighborhood effects.…”
Section: Discussionmentioning
confidence: 67%
“…For example, investigators in one study found that every increase of 10,000 unemployed people in the community was associated with a 1.2 percent decrease in preventive care utilization among the population with dental insurance in the Seattle area. 15 Similarly, investigators in other studies have found that a higher level of neighborhood poverty was associated with lower dental care utilization among adolescents 16 and Medicaid-enrolled children 17 even after they accounted for individual characteristics. A lower supply of dentists in a community also has been associated with a higher proportion of disadvantaged people in a community—namely, minorities and low-income people.…”
mentioning
confidence: 78%